Playing as a Bridge to Early Childhood Literacy: A Literature Review of Best Practices in Early Childhood Education - Latifah, Isna; Suriansyah, Ahmad; Amelia, Rizky (LPPM Universitas PGRI Semarang, 2025)
Early childhood literacy development is a critical foundation for future learning success. However, many early education practices still rely on teacher-centered approaches, with limited emphasis on meaningful play-based learning. This gap highlights the need for a comprehensive review of best practices that effectively integrate play into early literacy instruction. The fact remains that literacy levels in Indonesia are very low, and most of the population is unaware of it. This study aims to identify and analyze best practices in enhancing early childhood literacy through play-based approaches. Using the Literature Review method, relevant studies were selected, reviewed, and synthesized to explore patterns, similarities, and differences across various play-based literacy interventions. The data collection involved identifying peer-reviewed journal articles from reputable databases, followed by a structured analysis to extract key themes and strategies. The findings reveal that methods such as storytelling with puppets, letter-sound games, role-playing, and interactive literacy boards significantly boost children’s interest and literacy skills. Active engagement of children and the teacher’s role as a facilitator emerged as critical success factors. Nonetheless, challenges such as limited resources and a lack of teacher understanding of meaningful play hinder effective implementation. The study implies that targeted teacher training and the provision of supportive learning environments are essential to maximize the potential of play-based literacy learning.